Assessing The Impact of Color Vision Deficiency on Quality of Life in High School Students - Tarawifa, Susan; Jeane, Jessica; Nofri Enis, Rina; Ekaputri, Tia Wida; Putriyudi, Mandy (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Color vision deficiency (CVD) is a hereditary visual disorder that limits color discrimination and may affect daily functioning, learning performance, and psychosocial well-being. Despite its prevalence, awareness and screening among students in Indonesia remain low. Methods: A cross-sectional analytical study was conducted among 672 high school students selected through a cluster random sampling method. Color vision was evaluated using the Ishihara 38 Plates test, and quality of life was assessed using the Color Blindness Quality of Life (CBQoL) questionnaire, covering health, emotional, and daily activity domains. Data were analyzed using independent t-tests. Results: Of 672 participants, 24 (3.6%) had CVD, predominantly males (91.7%). The deutan type was the most frequent (75%). Students with CVD showed significantly lower CBQoL scores than those with normal color vision in health (3.50 ± 1.11 vs. 5.49 ± 0.54), emotional (3.64 ± 1.13 vs. 5.78 ± 0.35), and daily activity domains (3.71 ± 1.27 vs. 5.72 ± 0.45; p < 0.001). Conclusion: CVD significantly reduces students' quality of life. Early detection, educational adaptation, and awareness programs are essential in supporting students affected by these issues and promoting inclusive learning environments.